Assesmen Gizi Lansia Sebagai Upaya Untuk Mengidentifikasi Lansia Yang Beresiko Kekurangan Gizi - Siti Budi Utami; Setyowati; Maryana (Poltekkes Kemenkes Yogyakarta, 2022)
Increasing life expectancy is one of the successes of national development in the health sector. To improve the elderly well- being, we need an integrated and cross-sectoral program, such us a community service program. The purpose of this community service is to identify the elderly who are at risk of malnutrition. The activity was carried out by assessing the nutritional status of the elderly using Body Mass Index and nutritional assessment using Mini-Nutritional Assessment Short-Form. In addition, the elderly were given nutrition education. This program involved 35 respondents. The results showed that most of the elderly had normal nutritional status. However, the assessment also found respondents were at risk of malnutrition and obesity. Therefore, assessment of the elderly needs to be carried out periodically, so that malnutrition in elderly can be prevented.